Fun Learning Model Using the Padlet Application as an Effort to Increase the Effectiveness of Online Learning - Carlito da Costa; Antonino Pedro Marsal; Dulce Elda Ximenes Dos Reis (Budapest International Research and Critics University, 2022)
In the whole process of education in schools, learning is the most important activity. This means that the success of achieving educational goals depends a lot on how the learning process can take place effectively. This research is to increase the effectiveness of learning through fun learning on the online learning system at Al-Kautsar Elementary School Surabaya. The method used in this research is action research. Based on this research, it shows that there is an increase in the learning activities of fourth grade students at SD AL-Kaustar Surabaya through fun learning, this is indicated by an increase of 19.3% in the number of student attendance and an increase of 7% in the number of students who pay attention to the teacher's explanation. and there was a decrease of 6.87% in the number of students who turned off the camera during teaching and learning activities. an increase in the effectiveness of learning through fun learning with an increase of 7.87%, the use of padlet applications in fun learning can create a relaxed and pleasant atmosphere and can encourage positive emotions and arouse a sense of wanting to change in student behavior.